THE EFFECT OF EDUCAPLAY-BASED INTERACTIVE QUIZ ON STUDENTS' LEARNING INTEREST AND LEARNING OUTCOMES IN ELEMENTARY SCHOOLS - Rahmayanti, Jesica Dwi; Lailiyah, Siti; Setiaputri, Alvina Nanda (Auladuna: Jurnal Pendidikan Dasar Islam, 2024)
Abstract Learning interest is one of the components that determines the success or failure of learning. In the digital era, students are easily distracted by social networks, online games, or other cyberspace. The inability to process technology carefully will affect students' interest in learning. Teachers must be able to innovate to overcome students' low interest in learning, for example, by presenting interactive digital-based teaching media. This research aims to analyze the influence of Educaplay interactive quizzes on students' interest and Mathematics learning outcomes in class IV of SD Muhammadiyah 1 Menganti Gresik. This research is quantitative research with a quasi-experimental type. The sample consisted of 28 students in class IV-A. Questionnaires and tests are used in the data collection stage. Data analysis was carried out through the linear regression test stage with simultaneous F Test and Partial T Test assisted by the IBM SPSS Statistics Version 25.0 application. The research findings indicated that the data analysis obtained was significant for the variable of interest of 0.005 and a significance value for the learning outcome variable of 0.007. This result shows that the interactive quiz media of Educaplay affects students' learning interest and Mathematics learning outcomes in class IV of the Creative School of Muhammadiyah 1 Elementary School, Menganti, Gresik.